Respon Tokoh Lintas Agama Tentang AIDS di Palembang - Nugroho Nugroho; Zaki Faddad; Anisa Ramlan (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2020)
This research discusses on the Islamic group’s responses on the AIDS narratives in Indonesia. It is focused on the government and religious group responses on the AIDS phenomenon. Documentation and interview are used to find the data. This research finds that the Religious groups have determinant role to influence government’s actions to prevent the spreading of Aids in Indonesia. Finally, this article argues that the government programs to carry out the prevention of AIDS cannot escape from the moral based discourse on the disease. On the other hand, Religious leaders in Palembang vary in their perspectives on HIV/AIDS , some leaders consider that HIV/AIDS should be look into medical perspective, some views AIDS is the problem of morality.